2018
DOI: 10.1007/s11682-018-9909-x
|View full text |Cite
|
Sign up to set email alerts
|

Episodic memory decline in Parkinson’ s disease: relation with white matter hyperintense lesions and influence of quantification method

Abstract: The relation of white matter hyperintense lesions to episodic memory impairment in patients with Parkinson's disease (PD) is still controversial. We aimed at evaluating the relation between white matter hyperintense lesions and episodic memory decline in patients with PD. In this multicentric prospective study, twenty-one normal controls, 15 PD patients without mild cognitive impairment (MCI) and 13 PD patients with MCI were selected to conduct a clinico-radiological correlation analysis. Performance during ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…Parkinson's disease; white matter hyperintensities White matter hyperintensities (WMH), commonly associated with aging and cerebral small vessel disease, 1 have been observed on magnetic resonance imaging (MRI) of patients with Parkinson's disease (PD) 2 ; however, their exact role in clinical presentation and disease progression remains controversial. Although some studies demonstrate WMH to be significantly associated with a greater burden of motor dysfunction, mild cognitive impairment, and progression to dementia, [3][4][5][6][7][8][9][10] other studies have found no independent association beyond that of normal aging. [11][12][13][14][15][16][17][18] Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a monogenic form of cerebral small vessel disease with hallmark signs of WMH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parkinson's disease; white matter hyperintensities White matter hyperintensities (WMH), commonly associated with aging and cerebral small vessel disease, 1 have been observed on magnetic resonance imaging (MRI) of patients with Parkinson's disease (PD) 2 ; however, their exact role in clinical presentation and disease progression remains controversial. Although some studies demonstrate WMH to be significantly associated with a greater burden of motor dysfunction, mild cognitive impairment, and progression to dementia, [3][4][5][6][7][8][9][10] other studies have found no independent association beyond that of normal aging. [11][12][13][14][15][16][17][18] Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a monogenic form of cerebral small vessel disease with hallmark signs of WMH.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of these reports is further aggravated by the difficulty interpreting findings from studies using different cognitive assessments tools and approaches to measure WMH burden. 4,13 The main strength of our study was the ability to draw data from ONDRI's study design. ONDRI implemented a standardized multicenter, multiplatform approach that enabled the volumetric analysis of MRI-based neurovascular biomarkers and genomic information using validated quantification methods in their respective fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether these deficits are caused by the impairment of encoding or that of retrieval strategy remains controversial. Recently, a study showed that episodic memory function might be related to white matter hyperintense lesions 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, imaging and autopsy studies in PD patients have been used to probe for brain changes that predict and/or correlate with the severity of episodic memory impairment. These studies have identified thinning or decreased volume in hippocampus and in medial temporal and frontal lobe cortices ( 42 44 ) as well as increased total volumes of white matter hyperintense lesions in the frontal and temporal lobes ( 45 ) as promising candidates. Although less is known about the physiological processes that render episodic memory vulnerable in PD, there are reasons to suspect that biological sex and/or sex hormones play important roles.…”
Section: Introductionmentioning
confidence: 99%